2001
DOI: 10.1063/1.1391264
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced electronic energy transfer from v=0 of the E(0g+) ion-pair state in I2: Collisions with I2(X)

Abstract: Articles you may be interested inNon-adiabatic transitions from I2( E 0 g + and D 0 u + ) states induced by collisions with M = I2( X 0 g + ) and H2O J. Chem. Phys. 136, 234302 (2012); 10.1063/1.4725541Long-range collisional energy transfer between charge-transfer (ion-pair) states of I 2 , induced by H 2 O and I 2 ( X ) Electric-field-induced g/u mixing of the E0 g + ( 3 P 2 ) and D0 u + ( 3 P 2 ) ion-pair states of jet-cooled I 2 observed using optical triple resonanceThe collision-induced electronic energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…X0 þ g (aa) emission observed following excitation of E0 þ g ð 3 P 2 Þ ðv ¼ 0Þ under ASE conditions has a Gaussian envelope characteristic of emission from (v = 0). Under non-ASE conditions the spectrum contains emission from (v = 0-5) of the D0 þ u ð 3 P 2 Þ state [2]. We have reproduced both the ASE and non-ASE spectra.…”
Section: Vibrational Distribution Following Ase and Collisional Energmentioning
confidence: 56%
See 2 more Smart Citations
“…X0 þ g (aa) emission observed following excitation of E0 þ g ð 3 P 2 Þ ðv ¼ 0Þ under ASE conditions has a Gaussian envelope characteristic of emission from (v = 0). Under non-ASE conditions the spectrum contains emission from (v = 0-5) of the D0 þ u ð 3 P 2 Þ state [2]. We have reproduced both the ASE and non-ASE spectra.…”
Section: Vibrational Distribution Following Ase and Collisional Energmentioning
confidence: 56%
“…ASE transfer cannot explain this discrepancy as it will lead to an increase rather than a decrease in the rate constant, the reverse of the reported observations. In addition, Fecko et al [2] reported a rate constant for transfer from E0 þ g ð 3 P 2 Þ ðv ¼ 0Þ under non-ASE conditions of only 4 Â 10 À11 cm 3 s À1 . This discrepancy may, as suggested by Bibinov et al [4], be down to the response function of the detector system being accounted for in their experiment but not in the other two.…”
Section: Vibrational Distribution Following Ase and Collisional Energmentioning
confidence: 97%
See 1 more Smart Citation
“…[10][11][12][13] Double resonance excitation prepares bromine molecules in a single vibrational level of the E electronic state. [10][11][12][13] Double resonance excitation prepares bromine molecules in a single vibrational level of the E electronic state.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These studies have focused on the dynamics that accompany the collisions of I 2 following excitation to the E͑0 g + ͒ ion-pair ͑IP͒ state and document an important model system for examining nonadiabatic processes in molecules with dense rovibronic energy levels. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These studies have focused on the dynamics that accompany the collisions of I 2 following excitation to the E͑0 g + ͒ ion-pair ͑IP͒ state and document an important model system for examining nonadiabatic processes in molecules with dense rovibronic energy levels.…”
Section: Introductionmentioning
confidence: 99%